The Relationship of Early Breastfeeding Initiation (IMD) with Milk Fluency in Postpartum Breastfeeding Mothers at Klinik Pratama - Rena Fifta Atikatul Hasanah; Yessy Nur Endah Sari; Mega Silvian Natalia (Sean Institute, 2023)
The smooth production of breast milk is one of the supports for the fulfillment of nutritional intake, especially for infants. One of the efforts made by postpartum mothers to smooth breast milk production is by initiating early breastfeeding (IMD). The purpose of the study was to analyze the relationship between IMD and the smoothness of breast milk in postpartum breastfeeding mothers at Temu Waras Primary Clinic. The design of this study was correlative research with a cross-sectional approach. The population in this study were all postpartum breastfeeding mothers at Temu Waras Primary Clinic as many as 40 people. The sample size in this study amounted to 40 people taken by Accidental sampling. Data collection using a questionnaire then the data was processed using SPSS using the chi square test. The results of data analysis showed that Early Breastfeeding Initiation at Temu Waras Primary Clinic most of the respondents did early breastfeeding initiation as many as 28 people (70%) and Breast Milk Fluency at Temu Waras Primary Clinic most of the breast milk was fluent as many as 22 people (55%). Based on the chi square test, the significance value (Asymp. Sig) is 0.002 <0.05, meaning that ho is rejected and ha is accepted, so there is a relationship between IMD and breast milk fluency in postpartum breastfeeding mothers at Temu Waras Primary Clinic. It is recommended that mothers continue breastfeeding until the baby is 6 months old